The relation between attention deficit hyperactive disorder and substance use disorder among the juvenile offenders in a Malaysian detention centre / Suhana Muhamud @ Kayat - Suhana, Muhamud @ Kayat (2012)
Introduction: Attention deficit hyperactivity disorder (ADHD) is one of the most common childhood disorder which affect 3-9% of adolescents and up to 5% of adult. Research has shown that children with ADHD are at risk of involvement in crime. Comorbidity among attention deficit hyperactivity disorder (ADHD) and substance use disorder (SUD) is highly present in which one-half of adolescents with SUDs have ADHD. At present, there is no study in relation with ADHD and SUD done locally in the Malaysian Detention Centre. Objective: To determine the prevalence and co-relation of ADHD and substance use disorder among the juvenile offenders in Malaysian Detention Centre. This study also hopes to examine the socio demographic profile, association regarding family background and type of offences committed by the offenders with ADHD and substance use. v Methods: Juvenile offenders who were detained in Henry Gurney School, Telok Mas, Melaka was selected for this study. All juvenile ages below 18 years old were recruited. The sociodemographic data and family background was recorded using a questionnaire developed by the research team. Problem Orientated Screening Instrument for Teenager (POSIT) was given to screen subjects with substance use and at the same time measure any problem in physical health, mental health, family relations, peer relations, educational status, vocational status and social skills. Diagnosis of ADHD, Substance dependence and abuse and Alcohol dependence and abuse were made using Mini International Neuropsychiatric Interview for Children and Adolescents Version 6 (MINI-Kid). Result: There are total of 106 juvenile detainees who are less than 18 years old, 6 juveniles were excluded due to disciplinary problem. Therefore, only 100 subjects were recruited in the study. Majority of the subjects were male (90%), Malays (86%), had secondary level of education (84%) and employed (64%). 67% of the subjects had a diagnosis of ADHD with combined subtype is more prevalent and 77% of the subjects using substance. Chi square analysis showed 66.2% of subjects with ADHD have substance use disorder. However this result is not statistically significant (p=0.77). Most of the ADHD and substance use disorder subjects had family history of drugs, alcohol and criminality. However, it is shown to have statistically significant association between subjects with ADHD and family history of drugs (p=0.04) and alcohol (p=0.04). Student t-test analysis of POSIT score showed subjects with ADHD had statistically significant problem in vi social skills domain in moderate impairment and SUD subjects had statistically significant high-risk problems in substance use/abuse domain and moderate problems in family relations, peer relations, education, social skills and aggressive domain. In term of type of offence, there was no statistically significant association between ADHD subjects but showed statistically significant association with sex related crime (p=0.00) and substance use disorder even though the non sexual crime was higher than those who committed sexual related crime. Conclusion: In this study, there was no statistically significant association between attention deficit hyperactive disorder (ADHD) and substance use disorder (SUD) among the juveniles in Henry Gurney School, Melaka. Though clinically the comorbidity is highly present and it has a significant impact on functioning of the juvenile.